ISLAMIC LAW REVIEW USE OF SEX TOYS - Riady, Ahmad (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
This study aims to uncover how Islamic law observations of the tools used to meet the biological needs of humans, called sex toys, are lately used by many groups, both Muslim and non-Muslim, both inside and outside Indonesia, in this article the author will discuss the sex toys law in view of Islam starting from; First, the opinions of scholars in the four schools of thought on the use of sex toys as a medium to meet human biological needs in various conditions. Second, examine the arguments put forward by these schools and the way istidlal or istinbath law. Third, analyze the opinions that are most relevant to be held today with logical and istidlal arguments that are the closest to the truth between the proposition and the reality faced by people in this modern era.